(untitled) (MAUSAM, 2025)
This paper is concerned with the heavy rainfall episode reported over some locations of the eastern parts of Uttar Pradesh, India during 16 & 17 September 2021 and the associated meteorological conditions are investigated. Each heavy rainfall episode deserves major scientific documentation for the improvement in the existing knowledge of the concerned users. Even though it may also benefit the general public, as heavy rainfall concerns everybody in the domain. This case study will serve the above purpose and may be useful for policymakers, disaster managers, disaster response, and mitigation. Regarding the favourable meteorological conditions for heavy rainfall episode, it is found that synoptically there was an active Well Marked Low-Pressure system over the region. In addition, other conditions like positive relative vorticity, upper-level divergence, higher relative humidity, lower-level convergence, and vertical velocity (Omega) profiles also provided a favorable environmental mechanism. Continuous moisture supply from the Bay of Bengal through easterly/southeasterly winds extended up to middle tropospheric levels (500 hPa), which was another important factor for the occurrence of rainfall episodes. This case serves as an example that even in the absence of an active Jet core at 200 hPa over India, very heavy/extremely heavy rainfall may occur over east Uttar Pradesh.